ANTESEDEN DAN KONSEKUENSI PERILAKU DISFUNGSIONAL AUDITOR - Kiryanto -; Ayu Ning Tyas (Conference In Business, Accounting, And Management (CBAM), 2015)
This research aimed to obtain empirical evidence of the extent to which locus of control, organizational commitment, turnover intention, performance, time budged pressure, audit fee, of auditor dysfunctional behavior. And auditor dysfunctional behavior of influence the audit quality. The population in this study were all auditors working in public accounting firm in Semarang city in 2014. Sampling in this study using a convenience sample. Retrieval of data in this study using a questionnaire. Data were analyzed using multiple regression. The result of this research showed that all of the independent varialels influence the dysfunctional behavior so that increasing of locus of control, organizational commitment, turnover intention, performance, time budged pressure, audit fee can make dysfunctional behavior increase. On the contrary, decreasing of locus of control, organizational commitment, turnover intention, performance, time budged pressure, audit fee can make dysfunctional behavior decrease too. And dysfunctional behavior influence on audit quality. Key words : Dysfunctional Behavior, Audit Quality, Auditor Personal Characteristic, Locus Of Control, Time Budged Pressure, Organizational Commitment